Fatty Acids Activate the Transcriptional Coactivator YAP1 to Promote Liver Fibrosis via p38 Mitogen-Activated Protein Kinase - Salloum, Shadi; Jeyarajan, Andre J; Kruger, Annie J; Holmes, Jacinta A; Shao, Tuo; Sojoodi, Mozhdeh; Kim, Myung-Ho; Zhuo, Zhu; Shroff, Stuti G; Kassa, Andrew; Corey, Kathleen E; Khan, Sanjoy K; et al. (Cellular and molecular gastroenterology and hepatology, 2021)
Background & AimsPatients with simple steatosis (SS) and nonalcoholic steatohepatitis can develop progressive liver fibrosis, which is associated with liver-related mortality. The mechanisms contributing to liver fibrosis development in SS, however, are poorly understood. SS is characterized by hepatocellular free fatty acid (FFA) accumulation without lobular inflammation seen in nonalcoholic steatohepatitis. Because the Hippo signaling transcriptional coactivator YAP1 (YAP) has previously been linked with nonalcoholic fatty liver disease (NAFLD)–related fibrosis, we sought to explore how hepatocyte FFAs activate a YAP-mediated profibrogenic program. MethodsWe analyzed RNA sequencing data from a GEO DataSet (accession: GSE162694) consisting of 143 patients with NAFLD. We also performed immunohistochemical, immunofluorescence, immunoblot, and quantitative reverse-transcription polymerase chain reaction analyses (qRT-PCR) in liver specimens from NAFLD subjects, from a murine dietary NAFLD model, and in FFA-treated hepatic spheroids and hepatocytes. ResultsYAP-target gene expression correlated with increasing fibrosis stage in NAFLD patients and was associated with fibrosis in mice fed a NAFLD-inducing diet. Hepatocyte-specific YAP deletion in the murine NAFLD model attenuated diet-induced fibrosis, suggesting a causative role of YAP in NAFLD-related fibrosis. Likewise, in hepatic spheroids composed of Huh7 hepatoma cells and primary human hepatic stellate cells, Huh7 YAP silencing reduced FFA-induced fibrogenic gene expression. Notably, inhibition of p38 mitogen-activated protein kinase could block YAP activation in FFA-treated Huh7 cells. ConclusionsThese studies provide further evidence for the pathological role of YAP in NAFLD-associated fibrosis and that YAP activation in NAFLD may be driven by FFA-induced p38 MAPK activation.